Study of microRNA in relation to salt tolerance in banana (Musa acuminata ssp. malaccensis) / Seyed Hossein Beheshti - Beheshti, Seyed Hossein (2011)
Salinity is a major abiotic stress affecting crop productivity worldwide and results in millions of dollars in lost yield and damage to infrastructure. The purpose of this study was to identify microRNAs related to NaCl stress in Musa acuminata ssp. malaccensis (Ridl.). Sterilization techniques were employed to reduce contamination of embryos initiated from seeds. The germination rate of in vitro zygotic embryo culture was observed to increase to 92 % after soaking of the seeds in water (for periods of 2 or 3 days) compared to 72 % germination when no water treatment was used. Shoot induction and multiplications were carried out and 5mg/L BAP determined as the best concentration for shoot induction and multiplication. Different concentrations of sodium chloride (60, 80, 100, 120, 140, 160, 180, 200, 220 mM NaCl and 0 mM as a control) were used to determine the lethal concentration of NaCl and 120 mM was determined as the lethal concentration of NaCl for Musa acuminata ssp. malaccensis. The results were used to determine the stressed conditions for analysis of microRNAs and 100 mM of NaCl, the minimal inhibitory NaCl concentration for survival of banana plantlets was used for RNA extraction and construction of a salt stress small RNA library. Consequently measurement to assess the effect of salt stress on proline and elements (Na+, K+, Ca++, Mg++) accumulation in Musa acuminata ssp. malaccensis showed a clear correlation between increases in salt concentration and the concentrations of the different elements. The concentration of proline increased significantly in both root and leaves at 60 and 80 mM of NaCl concentration compared to the control with the highest amount of proline accumulation in both root and leaves recorded at 80 mM of NaCl. Elevation of NaCl concentrations also resulted in increasing Na+ and decreasing K+, Ca++ and Mg++ concentrations in Musa acuminata ssp. malaccensis. iii The optimized and modified RNA extraction method developed in this study resulted in the achievement of good quality and pure RNA with A260/280of 1.95. MicroRNA Discovery™ Kit (System Bio Sciences, USA) was then used for the isolation of microRNAs and a microRNA library was constructed by cloning the PCR products into PCR4-TOPO cloning kit (Invitrogen, USA). The titre of the library was estimated as 2000 recombinant clones and the DNA sequences of inserts from 45 recombinant clones were determined. Data were analyzed via Clustal W, BLAST and psRNA Target comparing with NCBI Genebank, miRBase and EST sequences data bases. Matches to the small library sequences included three different types of gene sequences (Salt stress, drought stress and BAP treated related), with high similarity to salt stress related gene from Oryza sativa and Hordeum vulgare, drought stress and BAP treated related genes from Oryza sativa. Therefore it is suggested that these small RNA library clones may be homologues from Musa acuminata ssp. malaccensis. Also mac-miR393 was found as a potential salt stress related miRNA homologue in Musa acuminata ssp. malaccensis.